Numerical simulation of the resistance braze welded assembly of a copper Inconel 601 ground electrode and a steel shell. (2nd August 2020) - Tahri, Chawki; Bertoni, Christophe; Feulvarch, Eric; Klocker, Helmut; Bergheau, Jean-Michel
Abstract: The ground electrode of spark plugs are assembled to a steel shell through a resistance braze-welding technique. Two types of currents can be used in that aim: AC or DC. Based on the current type, two different kinds of models were built. The first one is a 3-D magnetodynamic-thermal model, specially suited for AC current. The magnetodynamic and thermal FE analyses are weakly coupled to calculate the temperature distribution during the process. For the second model dedicated to DC currents, the temperature distribution during the process is obtained through a fully coupled 3-D electrokinetic-thermal modeling. The temperature distributions are then used to simulate the mechanical phenomena. The results of the different models are compared. The effects on the welded zone of the frequency (50 Hz and 5000 Hz), the regulation mode (current or voltage), and the spacing between copper and Inconel 601 coating are discussed.